2018
DOI: 10.1159/000494165
|View full text |Cite
|
Sign up to set email alerts
|

miR-136-5p Regulates the Inflammatory Response by Targeting the IKKβ/NF-κB/A20 Pathway After Spinal Cord Injury

Abstract: Background/Aims: miR-136-5p participates in recovery after spinal cord injury (SCI) via an unknown mechanism. We investigated the mechanism underlying the involvement of miR-136-5p in the inflammatory response in a rat model of SCI. Methods: Sprague-Dawley rat astrocytes were cultured in vitro to construct a reporter plasmid. Luciferase assays were used to detect the ability of miR-136-5p to target the IKKβ and A20 genes. Next, recombinant lentiviral vectors were constructed, which either overexpressed miR-136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Silencing of mir-136-5p significantly reduces these changes in protein expression and ameliorates the inflammatory cell infiltration and spinal cord damage. Therefore, mir-136-5p might be a new target for the treatment of Sci (45). in the present study, mir-136-5p expression was decreased in ea-treated Sci rats, compared with the Sci group.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Silencing of mir-136-5p significantly reduces these changes in protein expression and ameliorates the inflammatory cell infiltration and spinal cord damage. Therefore, mir-136-5p might be a new target for the treatment of Sci (45). in the present study, mir-136-5p expression was decreased in ea-treated Sci rats, compared with the Sci group.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, mirna-136-5p upregulates p-nuclear factor κB (p-nF-κB) expression by downregulating a20 expression, which causes astrocytes to produce inflammatory factors and chemokine factors, thus aggravating Sci (59). recently, deng et al (45) found that il-1β, il-6, TnF-α, interferon-α, inhibitor of nuclear factor kappa B kinase subunit β, and nF-κB in Sci rats were upregulated, while a20 was downregulated following miR-136-5p overexpression. Under these conditions, inflammatory cell infiltration into the rat spinal cord increases, significantly aggravating injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated astrocytes are the main source of all these factors: they account for about 30% of all cellular components; overexpression of the microRNA miR-136-5p in these cells during SCI is one of the inducers of proinflammatory factors and chemokines (primarily TNF-α and IL-1β) [ 26 , 27 , 28 ]. This process triggers an inflammatory immune response involving type 17 T-helpers [ 29 ].…”
Section: Immune and Cytokine Responses During The Acute Post-traummentioning
confidence: 99%
“…XAN signi cantly inhibited the proliferation of RA-FLS cells by inhibiting IκκB/NF-κB and downstream target proteins [16]. Silencing miR-136-5p signi cantly reduced the levels of IL-1, IL-6, TNF-α, IFN-α, IκκB and NF-κB and ameliorates the in ammatory cell in ltration and damage to the spinal cord [17]. These ndings indicated that the IKKβ/NF-κB signal pathway participated in the proliferation and in ammation in RA-FLS cells.…”
Section: Introductionmentioning
confidence: 99%